Unusual Presentation of Differentiated Thyroid Cancer Metastasis - Iftikhar, Haissan; Ikram, Mubasher; Muhammad, Adnan Yar; Nathani, Karim Rizwan (International Archives of Otorhinolaryngology, 2018)
Introduction The rates of thyroid cancers are on a rise, especially well-differentiated thyroid cancers. This could be partly due to newer diagnostic modalities, like high-resolution ultrasound, that can pick up smaller lesions. Differentiated thyroid cancers with distant metastases are not common, and even rarer is the initial presentation with complaints not related to the neck.Objectives The objective of this series was to study and report the unusual cases of patients with differentiated thyroid cancer with distant metastasis. There is a lack of data in the literature on these cases, and due to the rarity of such metastases, no definite treatment protocol has been defined.Methods A retrospective chart review of 1,200 cases of thyroid surgeries was performed. A total of 10 cases of well-differentiated thyroid cancer on the final histopathology exam that had initially presented with usual complaints to departments other than the Otolaryngology Department were identified.Results A total of 6 patients had papillary carcinoma, whereas 4 patients had follicular carcinoma on final the histopathology exam. Two patients presented with iliac crest lesions, 2 with vertebral lesions one each with parapharyngeal mass, supraclavicular mass, labia majora swelling and bleeding, lung, rib and neck of femur lesion.Conclusion There are still no specific guidelines on how to address these patients with differentiated thyroid cancer with distant metastasis (except for the cases of bone and lung lesions) and on which treatment should be offered in case of recurrence. More studies on the subject are required.
Keywords: thyroid neoplasm; neoplasm metastasis; thyroid nodule